Urbanism and History: Two Interpretative Keys of the Reception of Ernesto Volkening to Gómez Dávila (2023)
Initially, this article examines Ernesto Volkening’s critical reading and hermeneutic consideration of Nicolás Gómez Dávila’s work. After presenting the interpretive guidelines in Volkening’s Diario de lectura, the authors’ interests in modern architecture and urbanism are analyzed as keys to criticizing our reifying way of life. Subsequently, guidelines that address history and historicity are provided, under the implied notion of a hermeneutic understanding exemplified by context, unbinding from any determinism, and embodying a singularity and individuality.